Analisis kelumit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK The trace analysis method is developed to analyze specific samples and their elements. The small amount of samples or the very small concentrations of elements in very large matrices necessitates the use of this method. A dust free laboratory, equiped with a screened laminar air supplyed chamber and highly purified water and chemicals, is required for trace analysis. The main problem is contamination from the surroundings, Chemicals and equipment.